Desenvolvimento de métodos de preparo de amostras de erva-mate para a posterior determinação de As, Cd e Pb por GF AAS e ICP-MS - Pardinho, Renan Buque (2016)
In this work, the following methods for yerba mate digestion/extraction for further determination of As, Cd and Pb by graphite furnace atomic absorption spectrometry (GF AAS) and/or inductively coupled plasma mass spectrometry (ICP-MS) were evaluated: i) wet digestion in open systems ii) wet digestion in closed systems iii) microwave-assisted wet digestion (MAWD) using diluted HNO3 and O2 as auxiliary reagent and iv) ultrasound-assisted extraction (UAE). For the wet digestion method using open and closed systems by conventional heating, the digestion efficiency for several sample masses and HNO3 volume were evaluated in the both systems. For methods “i” and “ii”a low digestion efficiency was observed than the open system was used allowing a high throughput and not necessary predigestion step. The GF AAS technique was used for As, Cd and Pb determination due to the low digestion efficiency of open system method and to avoid possible interferences in the determination step. For MAWD using diluted HNO3 with O2 as auxiliary reagent, several sample masses, variable amount of O2 in gaseous phase and different flow-rates during digestion process were evaluated. After the MAWD evaluation using diluted HNO3 with O2 as auxiliary reagent it was possible to use a relatively high yerba mate mass (1500 mg). For high of sample mass the digestion was not observed influences in the efficiency digestion for different amount of O2 in gaseous phase. On the other hand, it was observed an improvement in the digestion efficiency when the maximum flow-rate allowed by equipment was used. However this condition could cause problems in equipment. For the determination step by ICP-MS it was necessary an interference study due to the high carbon content in solution. For the UAE, extractant solution, sonication time, temperature and sample mass were evaluated. Regarding the recovery of As, Cd and Pb, antagonist effects were observed when sample masses higher the 1000 mg were used. The limit of quantification obtained for three methods evaluated were lower than those established in legislation. Therefore, the proposed methods were considered as feasible for yerba mate digestion/extraction for further determination of As, Cd and Pb by GF AAS and/or ICP-MS.